Dinamika Kelompok Perkumpulan Petani Pemakai Air (P3A) Sumber Mulyo dalam Kegiatan Pengelolaan Jaringan Irigasi di Desa Pereng Kecamatan Mojogedang Kabupaten Karanganyar - Azmul Fauzi; Joko Winarno; Sapja Ananta (AGRITEXTS: Journal of Agricultural Extension, 2021)
The purpose of this research are to know the factors of that affect group dynamic, the result of activities, and the best strategy in development object of this research. This research use indept revew, observation, and document analyst to collecting the datas. And then, the datas will be thought in input stage until the researcher fing the strengths and the weakness of the object. The researcher can find the opportunities and the treats of thi object by using IFE (Internal Factor Evaluation) matrix and EFE (External Factor Evaluation) matrix. The researcher use SWOT (Strengths, Weaknesses, Opportunities, and Threats) matrix to determine the strategies that will be use in the next stage. The result of the research is the most important strength factors are high farmer participation and participatory of the leadership (0,727). While, the weaknesses are low farmer education and the existence of multiple positions in management (0,409). The highest opportunity is attention from the government at the beginning of P3A activities (1,333). While the threat factor is the lack of government attention to the current P3A activities (1,000). The result of this research is the strategies can be used for P3A Sumber Mulyo’s activities are optimizing P3A Sumber Mulyo activities to faced the problem. The researcher hope to P3A Sumber Mulyo can solve the problem about primary, secondary, and tertiary waterways management and manufacturing and processing of organic fertilizer.